FAKTOR-FAKTOR YANG MEMPENGARUHI KETERLAMBATAN DIAGNOSIS DIABETES MELITUS TIPE 2 DI WILAYAH KERJA PUSKESMAS ABANG I, KABUPATEN KARANGASEM BALI TAHUN 2015 - Kumudini Subramaniam (DiscoverSys Inc., 2016)
Diabetes Mellitus (DM) Type 2 is one of disease that has attraction around the world in which one of the main problem is the delay in the diagnosis of the disease. The delay in the diagnosis of DM can also be found in Abang I Health Centre. In the year of 2014, there is a total of 34 new cases of DM and 74% were diagnosed DM for the first time since has come with complications such as gangrene, retinopathy, and nephropathy. However, no information or previous research that may explain the reason why this delay occurred in Abang I Health Centre. This study aims to determine the factors that influence the delay in diagnosis of type 2 diabetes mellitus in the working area of Abang I Health Centre, Karangasem District. This study is a qualitative study with in-depth interviews among six patients that already had complication for the first time when diagnose with DM and focus group discussion (FGD) among four healthcare workers in Abang I Health Centre that has relationship with the service given to DM patient. The results showed that the factors affecting the delay in diagnosis of type 2 diabetes mellitus in the working area of Abang I health centre consists of limitation of knowledge among the community about diabetes mellitus, the negative perception of diabetes mellitus among the community, misperception of early medical examination, lack of trust among the community towards the quality of health care service, diabetes mellitus is not of the priority for health care and lack of recommendation for the early detection of diabetes mellitus from the health care workers. Based on the findings, the healthcare centre should increase the promotion of health about DM disease through media communication and education (KIE) that is easily accessed by the community besides adding non-infectious diseaseinto one the main priority work agenda in Abang I Health CentreÂ